PELATIHAN CRITICAL THINKING BERBASIS KISAH NABI IBRAHIM DALAM AL-QUR’AN DI PONDOK PESANTREN MODERN RADEN PAKU TRENGGALEK - Afrizal Syahputra; Abduloh Safik; M. Fathun Nadhor (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
This community service activity aims to enhance the critical thinking abilities of teachers and Final-year students at Raden Paku Modern Islamic Boarding School (Trenggalek) through an approach based on the story of Prophet Ibrahim in the Qur’an. The story of Prophet Ibrahim was chosen because it contains deep reflective, rational, and spiritual values, and is highly relevant for fostering a culture of analytical and argumentative thinking within the pesantren environment. The methods used in this activity included several stages: identifying problems and partner needs, planning, implementation of the training, evaluation, and follow-up planning through a service-learning approach. The results of the program indicate an improvement in participants’ ability to identify arguments, think logically, and connect faith-based values with rational thinking. This activity successfully fostered an awareness that critical thinking is not a form of resistance to religious doctrine, but rather part of the search for deeper faith and meaning, as exemplified by Prophet Ibrahim.